A brief recent history of the epidemiology of congenital syphilis in the United Kingdom. (October 2018) - Simms, Ian; Goh, Beng T; French, Patrick; Wallace, Lesley A; Irvine, Neil; Thomas, Daniel Rh; Winter, Andrew J; Lyall, Hermione; Webb, Sharon
Within a century, congenital syphilis has been reduced from a major cause of morbidity and mortality to a condition rarely seen in the UK. Here, newly-derived literature and information searches were used to create a contemporary overview of the epidemic, including its epidemiology. Although constrained by high-quality healthcare services and with an incidence below the World Health Organization elimination threshold, congenital syphilis still has the potential to cause major consequences for the health and life chances of affected infants. If the complex challenges presented by this preventable disease are to be resolved, intervention strategies need to be optimised, rigorously assessed and extended across Europe.